Application of Secondary Metabolites of Two Pseudomonas fluorescens Isolates to Control Bacterial Wilt of Potato - Soesanto, Loekas; Dwijayanto, Haris; Mugiastuti, Endang; Manan, Abdul (KnE Life Sciences, 2022)
The focus of this research was to determine how secondary metabolites from two isolates of Pseudomonas fluorescens (P8 and P60) affected potato plant resistance to bacterial wilt (Ralstonia solanacearum) as well as potato growth and productivity. For four months, this experiment was carried out at Serang Village’s potato field, in Karangreja District, Purbalingga Regency, at an altitude of 1285 m above sea level, with Andisol soils, an average temperature of 22.31 C, and relative humidity of 84.09%. A randomized block design was used with a control treatment, drenching with 1.5 g/L bactericide (20% streptomicin sulphate) administered six times, and drenching with secondary metabolites of P. fluorescens P8 or P. fluorescens P60 administered three, six, nine, and 12 times. Each treatment was carried out five times. Each treatment resulted in a different incubation period, disease intensity, infection rate, plant height, number of tubers, tuber weight per plant, wet and dry weight of crop, fresh and dry weight of root, number of branches, and phenolic compound analysis. The results showed that applying P. fluorescens P8 and P. fluorescens P60 secondary metabolites to potato plants can induce resistance by increasing the content of phenolic compounds in the plants. Drenching with secondary metabolites from P. fluorescens P8 or P. fluorescens P60 12 times can reduce the incubation period by 9.23%, the intensity of disease by 75%, and the incidence of disease by 53.57%. Plant height, crop dry weight, root fresh weight, root dry weight, number of tubers, and tuber weight per plant can all be increased by using secondary metabolites. Keywords: bacterial wilt, potato, Pseudomonas fluorescens, secondary metabolites.